Dynamic Analysis of a Delayed Fractional Infectious Disease Model with Saturated Incidence - Peng Ding; Zhen Wang (Fractal and Fractional, 2022)
This paper addresses a new fractional order infectious disease model with saturated incidence and time delay. In the new model, the isolated population and the asymptomatic infected population are considered. The invariant region and positive analysis of the solution of the model are established. Next, the basic reproduction number is obtained by the next-generation matrix method, and the sufficient conditions for local asymptotic stability for arbitrary time delays are proposed. Finally, the correctness of the theoretical results is verified by some numerical simulations.